2020
DOI: 10.1111/ppe.12672
|View full text |Cite
|
Sign up to set email alerts
|

Advanced maternal age and risk of adverse perinatal outcome among women with congenital heart disease: A nationwide register‐based cohort study

Abstract: Background: Women with maternal congenital heart disease have a higher risk of preterm birth (PTB) and giving birth to a small for gestational age (SGA) infant. Advanced maternal age (≥35 years) likewise increases the risk of PTB and SGA, probably explained by poorer cardiovascular status. It is likely that advanced maternal age is particularly detrimental in women with congenital heart disease. Objectives: We aimed to determine whether the pattern of higher risk of PTB and SGA with higher maternal age varied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“… 25 To limit the risk of misclassification of CHD all diagnoses of CHD were validated using an algorithm previously described. 7 , 8 , 31 Likewise, the positive predictive value of the included cardiovascular outcomes is in general high in the Danish National Patient Register for both cardiovascular diagnoses 27 , 45 , 46 , 47 and cardiac procedure and surgery codes. 48 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 25 To limit the risk of misclassification of CHD all diagnoses of CHD were validated using an algorithm previously described. 7 , 8 , 31 Likewise, the positive predictive value of the included cardiovascular outcomes is in general high in the Danish National Patient Register for both cardiovascular diagnoses 27 , 45 , 46 , 47 and cardiac procedure and surgery codes. 48 …”
Section: Discussionmentioning
confidence: 99%
“… 37 , 38 , 39 , 40 We defined the subgroup of individuals having obstetric complications as gestational diabetes, preeclampsia, and/or gestational diabetes as they are common obstetric complications and were present before start of follow‐up (date of delivery). However, fetal outcomes such as preterm birth and infants born small for gestational age, which is also more common among women with CHD, 6 , 7 , 8 , 9 , 41 have also been associated with adverse long‐term cardiovascular health in the general population of pregnant women. 37 , 38 , 39 It is, however, debated whether the pregnancy per se causes the higher risk of obstetric complications or the pregnancy unmasks a predisposing condition and the pregnancy thereby acts as a cardiovascular stress‐test.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A longer admission after delivery among women with CHD can be a consequence of several factors that are more common among women with CHD than among women without CHD, e.g. a higher proportion of preterm birth [ 8 , 9 , 11 , 14 , 17 ], obstetric complications or cardiac complications during pregnancy and delivery [ 7 , 10 , 17 , 34 , 35 ]. It could involve a pathway from CHD to obstetric complications during pregnancy and delivery leading to a higher frequency of cesarean section and longer hospital stay.…”
Section: Discussionmentioning
confidence: 99%
“…Most women with CHD will be able to complete a pregnancy, despite a larger proportion of women with CHD experiencing more cardiac, obstetric, and neonatal complications compared to women without CHD [ 7 11 ]. Several American studies have also shown an association between CHD and length of hospital stay after delivery [ 6 , 7 , 12 16 ] which might reflect a more complicated delivery [ 12 ], a greater proportion of deliveries by cesarean section [ 5 , 7 , 11 , 12 , 17 , 18 ] and more preterm births [ 7 9 , 11 , 17 ] that result in hospitalization, or healthcare workers’ precautions for early discharge of women with known CHD. However, in a setting with user paid healthcare the length of hospital stay might also be influenced by insurance status and socioeconomic position [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%